2021
DOI: 10.1155/2021/6673661
|View full text |Cite
|
Sign up to set email alerts
|

W196 and the β‐Hairpin Motif Modulate the Redox Switch of Conformation and the Biomolecular Interaction Network of the Apoptosis‐Inducing Factor

Abstract: The human apoptosis-inducing factor (hAIF) is a moonlight flavoprotein involved in mitochondrial respiratory complex assembly and caspase-independent programmed cell death. These functions might be modulated by its redox-linked structural transition that enables hAIF to act as a NAD(H/+) redox sensor. Upon reduction with NADH, hAIF undergoes a conformational reorganization in two specific insertions—the flexible regulatory C-loop and the 190-202 β-harpin—promoting protein dimerization and the stabilization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In contrast to full‐length MIA40/CHCHD4, the dissociation constant of the AIFM1‐CHCHD4/MIA40 peptide interaction was an order of magnitude higher (K D = 2.94 μM, Appendix Fig S8K) indicating that other regions in MIA40/CHCHD4 might contribute to binding strength. Our findings are in line with previous results (Hangen et al , 2015; Romero‐Tamayo et al , 2021) and extend them by showing that MIA40/CHCHD4 and AIFM1 form a stable long‐lived complex with a 1‐to‐2 stoichiometry in the presence of NAD(P)H.…”
Section: Resultssupporting
confidence: 93%
“…In contrast to full‐length MIA40/CHCHD4, the dissociation constant of the AIFM1‐CHCHD4/MIA40 peptide interaction was an order of magnitude higher (K D = 2.94 μM, Appendix Fig S8K) indicating that other regions in MIA40/CHCHD4 might contribute to binding strength. Our findings are in line with previous results (Hangen et al , 2015; Romero‐Tamayo et al , 2021) and extend them by showing that MIA40/CHCHD4 and AIFM1 form a stable long‐lived complex with a 1‐to‐2 stoichiometry in the presence of NAD(P)H.…”
Section: Resultssupporting
confidence: 93%
“…Under physiological conditions, the activity of the IMS disulfide relay might be influenced by different factors including the availability of oxidized cytochrome c, the availability of oxygen, and the activity of the respiratory chain. In addition, recent work has demonstrated that the disulfide relay is sensitive to changes in IMS NADH levels through the oxidoreductase function of its core component AIFM1 ( Hangen et al, 2015 ; Romero-Tamayo et al, 2021 ; Salscheider et al, 2022 ). AIFM1 requires NADH binding to undergo dimerization.…”
Section: Discussionmentioning
confidence: 99%
“…Its key component is the oxidoreductase MIA40/CHCHD4, which directly interacts with and oxidizes incoming substrate proteins ( Banci et al, 2009 ; Hofmann et al, 2005 ; Mesecke et al, 2005 ; Rissler et al, 2005 ). In human cells, the soluble MIA40/CHCHD4 forms a permanent trimeric complex with the IMM-anchored protein AIFM1 ( Elguindy and Nakamaru-Ogiso, 2015 ; Hangen et al, 2015 ; Herrmann and Riemer, 2020 ; Meyer et al, 2015 ; Romero-Tamayo et al, 2021 ; Salscheider et al, 2022 ; Susin et al, 1999 ). The binding of MIA40/CHCHD4 by AIFM1 is crucial for its activity and only takes place if AIFM1 dimerizes, which it does in an NADH-dependent fashion ( Romero-Tamayo et al, 2021 ; Salscheider et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On its part, CypA would specifically associate to the 370 to 394 amino acid region within the NADH-binding domain of H. sapiens AIF ( 15 ). Finally, AIF interacts with DNA in a sequence-independent manner based on electrostatic interactions around a positively charged protein crown ( 10 , 16 ). However, up to date no in vitro or in vivo evidence exists for the formation of this nuclear chromatinolytic degradosome complex, despite a plausible theoretical molecular model ( 14 ).…”
Section: Introductionmentioning
confidence: 99%